Több gép vagy nagyobb hatékonyság? Növekedés, tőkeállomány és termelékenység Magyarországon 1995-2013 között - István Kónya (Hungarian Academy of Sciences, Institute of Economics, 2015)
– The paper recalculates total factor productivity (TFP) in Hungary, and based on this, presents an updated decomposition of GDP growth. Compared to the previous literature on Hungary, contributions include the quantification of human capital and the inclusion of the capacity utilization of production inputs. The latter is necessary to get a more realistic picture of productivity fluctuations. Results show that both increases in the capital stock and improvements in productivity contributed to Hungarian growth, while the role of human capital, and employment in particular was only important at the end of the 90's. The analysis attempts to take into account possible connections between capital deepening and productivity. In our neoclassical framework we can only explore the possibility of TFP induced capital investment, leaving the study of reverse causality for future research.
Keywords: O47; E01; E25; J21; 330; economic growth; TFP; Hungary; human capital; capacity utilization